APLIKASI ENSIKLOPEDIA HALAL DAN HARAM DALAM ISLAM MENGGUNAKAN FRAMEWORK CODEIGNITER (Information Technology and Telematics, 2014)
Abstract - Know and learn things halal and haram in termsof food and drink is an obligation for Muslims. Encyclopediausually describes a specialized in one particular branch ofscience which is arranged alphabetically, categories orvolume of issue and generally printed in the form of a seriesof books. Study of halal and harm's law on food and drinks inbook form has several constraints These constraints were thedeficiency of the time and place because there are onlycertain places, the availability of books and literature arelimited.. To resolve the issue, a solution in the form of asingle application of halal and harm in the encyclopedia ofIslam-based web that aim to facilitate the study of food anddrink where the application can be accessed via the mediumof the internet..This application development using the methodWaterfall. The design of the system using the contextdiagram, DFD Level 0, DFD Level 1 and ERD. A websitecreated using the framework Codeigniter, MySQL databaseand PHP programming language.Current the application of encyclopedia halal andharam in islam based web using a paid domain withwww.halaldanharam.info so that the data is available more.Keywords: Encyclopedia, halal, haram, food, drink,framework Codeigniter.